Clinical value of serum trophoblast cell surface protein 2 (TROP2) antibody in non-small-cell lung cancer patients. (16th November 2016) - Zheng, Zhuan; Dong, Xue-Jun
Abstract: Objective: This study was to explore the clinical role of serum trophoblast cell surface protein 2 (TROP2) antibody in patients with non-small-cell lung cancer (NSCLC). Materials and methods: We collected serum specimens from 117 NSCLC patients, 40 benign lung disease patients, and 60 healthy controls. TROP2 antibody concentrations were measured using enzyme-linked immunosorbent assay. Results: Serum TROP2 antibody levels were higher in the NSCLC group compared to the control group ( p < 0.001). TROP2 antibody, at a cutoff value of 9.8 U/ml, showed good diagnostic performance for NSCLC. Conclusion: Measurement of TROP2 antibody might have diagnostic value for patients with NSCLC.